SOME PROPERTIES FOR CERTAIN SUBCLASSES OF ANALYTIC FUNCTIONS INVOLVING DERIVATIVE OPERATOR - Eljamal, Ebtisam Ali; Darus, Maslina (MATTER: International Journal of Science and Technology, 2015)
In this paper, we introduce a subclass of analytic functions by using the subordination concept between this function and generalized derivative operator. Some interesting properties of this class are obtained.